Pengaruh Thought Stopping Therapy Terhadap Tingkat Kecemasan Remaja - Resanti, Siska Dwi; Saifudin, Moh.; Rokhman, Abdul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Adolescents represent an age group highly susceptible to anxiety due to academic pressures, social dynamics, and complex psychological changes. If left unmanaged, anxiety can negatively impact mental health and academic performance. This study aims to investigate the effect of thought stopping therapy on anxiety levels among adolescents at SMPN 1 Lamongan. A pre-experimental research design was employed using a one-group pre-test and post-test approach. A total of 35 adolescents were selected through purposive sampling based on specific inclusion criteria from a population of 350 students. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and analyzed using the Wilcoxon Signed Rank Test.Prior to the intervention, all participants (100.0%) exhibited moderate anxiety levels. Following the therapy, nearly all participants (97.1%) showed no symptoms of anxiety. The Wilcoxon test yielded a Z-score of -5.169 with a significance level of p = 0.001, indicating a statistically significant difference in anxiety levels before and after the intervention. These results demonstrate that thought stopping therapy has a significant effect on reducing anxiety among adolescents. It proves to be an effective method for helping individuals manage anxiety independently.Therefore, thought stopping therapy is recommended as a psychological support strategy within school environments. Adolescents are encouraged to continue practicing this technique independently in their daily lives—especially when confronted with anxiety-triggering situations—so it may become an integral part of their coping mechanisms.